Detecting online recruitment fraud by using machine learning - Ghosh, Gitanjali; Tabassum, Hridita; Atika, Afra; Kutubuddi, Zainab (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.